The Persistent Challenge of Unemployment in Pakistan: A Quantitative Analysis of its Determinants (Journal of Asian Development Studies, 2025)
Unemployment is a global issue affecting most countries, and Pakistan is no exception. Unemployment in Pakistan is a major and long-lasting problem that impacts people's lives, the economy, and society. The persistence and severity of the issue motivate us to investigate the potential macroeconomic factors that affect Pakistan's unemployment rate. The main factors analyzed in this study are GDP, trade, technical cooperation grants (TCG) and inflation. TCG is included in the unemployment model for the first time. Including inflation and GDP in the model helped revisit the implications of Okun's Law and the Phillips curve. ARDL is used to account for long-term and short-term effects over the period 1980 to 2022. The findings reveal that GDP and trade have a significant and negative impact in the long run; a 1% raise in GDP results in 17 17-point decreases in unemployment, and a 0.81% decrease in unemployment occurs when trade is raised by 1%. TCG and inflation were found to have an insignificant effect on unemployment in the long run, but TCG shows a significantly negative impact in the short run. The results imply that reassessing and enhancing the efficacy of TCG programs, trade liberalization, economic expansion and generating employment opportunities should be given priority to bring down Pakistan's unemployment rate.